International corporate governance - John, Kose; Makhija, Anil K. (Emerald, 2011)
Volume 14 of Advances in Financial Economics presents recent research on corporate governance from a number of countries across the world, including the United States, Spain, Malaysia, Israel and others. Many important corporate governance mechanisms are examined, such as board characteristics (size, independence, duality, staggered form), ownership structure, legal protection of shareholders, annual general meetings, and executive compensation. The findings have implications for mergers and acquisitions, IPOs, related party transactions, CEO pay, volume of trading and stock volatility, and underwriting. Thus, the implications of corporate governance for firm performance and shareholder experience are covered through the salient activities of firms.
Keywords: Business & Economics -- Economics -- Comparative.; Business & Economics -- Finance.; International finance.; Financial crises & disasters.; Corporate governance.; elektronické knihy; electronic books